1973
DOI: 10.1159/000467989
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Effects on Magnesium Metabolism in Rats

Abstract: Administration of lithium chloride to rats increased serum magnesium. The distribution of injected 28 Mg was also changed by lithium: radioactivity in serum was increased, radioactivity in bone was decreased. The results were similar to those which could be obtained with radioactive calcium. It is suggested that the results were secondary to lithium effects on carbohydrate metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Also, Mellerup et al (1973) showed an increase in plasma magnesium after a single intraperitoneal injection of 900 ,umol of lithium chloride which is comparable to the increased magnesium level we obtained with a very different dosage and route of administration.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, Mellerup et al (1973) showed an increase in plasma magnesium after a single intraperitoneal injection of 900 ,umol of lithium chloride which is comparable to the increased magnesium level we obtained with a very different dosage and route of administration.…”
Section: Discussionsupporting
confidence: 86%
“…Comparing the results of the present study with those of Birch & Jenner (1973), both show a decrease in brain magnesium proportionally depending on the dose of lithium, although in the latter case lithium was administered by intraperitoneal injection or in the drinking water. Also, Mellerup et al (1973) showed an increase in plasma magnesium after a single intraperitoneal injection of 900 ,umol of lithium chloride which is comparable to the increased magnesium level we obtained with a very different dosage and route of administration.…”
Section: Discussionsupporting
confidence: 86%
“…A number of reports have shown that lithium treatment is accompanied by increased plasma magnesium concentrations (Nielsen, 1964;Bunney, Goodwin, Davies & Fawcett, 1968;Aronoff et al 1971;Andreoli et al 1972;Birch & Jenner, 1973;Mellerup et al 1973). Birch & Jenner (1973) reported that in rats lithium apparently leads to a reduction in brain magnesium at the same time that plasma magnesium levels are increased.…”
Section: Discussionmentioning
confidence: 99%
“…Baer, Kassir & Fieve (1970) ;Ho, Gershon & Pinckney (1970); and Birch & Jenner (1973) found that chronic administration of lithium to rats results in a significant decrease in brain sodium concentration. An increase in serum magnesium concentration has also been observed to accompany treatment with lithium (Nielsen, 1964;Aronoff et al (1971); and Andreoli, Villani & Brambilla, 1972;Mellerup, Plenge & Rafaelsen, 1973;and Birch & Jenner, 1973). Therefore, the effect of lithium on the metabolism of electrolytes in the C.N.S.…”
Section: Introductionmentioning
confidence: 98%
“…The results concerning the effect of lithium on calcium and magnesium metabolism seem conflicting. Some groups have found an increase in serum calcium (Mellerup et al (1970(Mellerup et al ( , 1973, Andreoli et al (1972), Birch & Jenner (1973), Christiansen et al (1975a) and serum magnesium ( Nielsen (1964), Aronofl et al (1971( ), Christiansen et al (1975a, Transbll et al (1977)) during lithium treatment, while others have failed to confirm these changes (Tupin et al (1968), Hennernann & Zimmerberg (1974). None of these reports has taken into consideration the unipolar/bipolar distinction.…”
Section: Leonhard'smentioning
confidence: 98%